APPLICATION OF THE HEALTH BELIEF MODEL ON ACCEPTANCE OF THE HPV VACCINE IN PREVENTION OF CERVIC CANCER IN STUDENTS OF SMP NEGERI 1 DENPASAR - Purnama Sari, I Dewa Ayu Widya; Ariastuti, Luh Putu; Kartika Sari, Komang Ayu; Sucipta Putri, Wayan Citra Wulan (E-Jurnal Medika Udayana; Vol 11 No 7 (2022): E-Jurnal Medika Udayana, 2022)
Cervical cancer is a malignant disease of the cervix that is triggered by infection with the Human Papilloma Virus (HPV). An effective way to prevent cervical cancer is the HPV vaccination. The success of vaccine acceptance depends on various factors that can be categorized into, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. According to data from the Denpasar City Health Office, as many as 31 junior high schools in Denpasar have not received the HPV vaccination program, one of which is SMP Negeri 1 Denpasar. This study aims to determine how the implementation of the Health Belief Model on the acceptance of the HPV vaccine in students of SMP Negeri 1 Denpasar. This research is an analytic observational research with cross sectional method. The data was obtained from questionnaires via google forms. The data were processed using the chi-square statistical test. From the results of the study, respondents have a high perception of susceptibility (50.9%), severity (52.6%), benefits (52.6%), barriers (57.9%), cues to action (62.3%), and self-efficacy (60.5%). The correlation test results show that there is a significant relationship between the implementation of the health belief model and acceptance of the HPV vaccine. Based on the results of the study, to increase the acceptance of the HPV vaccine, health workers should look for alternatives in providing services and information related to the benefits of the HPV vaccine so as to increase good perception in health belief model.